Distributed Data-Centric Application Logic Layer = Warstwa rozproszonej logiki aplikacji skoncentrowanej na danych - Turchan, Krzysztof; Piotrowski, Krzysztof (Zielona Góra: Uniwersytet Zielonogórski, Instytut Metrologii, Elektroniki i Informatyki)
EDGElevel architecture has been proposed in response to the attempt to move cloud computing to distributed computing on Internet of Things (IoT) devices. A key element of this architecture is the modular tinyDSM/SmartDSM middleware, which enables efficient data exchange across heterogeneous sensor networks. However, the Distributed Data-Centric Application Logic Layer plays a key role, enabling data aggregation, pattern recognition, parallel processing and efficient real-time processing.
Keywords: komputeryzacja; przyrządy pomiarowe; informatyka; technologie informacyjne